Structural concrete : theory and design - Hassoun, M. Nadim; Al-Manaseer, A. A. (Wiley, 2020)
"This concrete structural design and analysis textbook has been a go-to resource for structural engineering students and professionals for over twenty years. Newly updated to reflect the latest ACI 318-19 code, this seventh edition emphasizes student comprehension by presenting design methods alongside relevant codes and standards. Numerous examples and practice problems guide students through the analysis and design of each type of structural member, and all examples are presented using SI units and US-SI conversion factors. New to this edition are code provisions for transverse reinforcement and shear in wide beams, hanger reinforcement, and bi-directional interaction of one-way shear. This seventh edition also includes the latest information on two-way shear strength, ordinary walls, seismic loads, reinforcement detailing and analysis, and materials requirements. Instructors have access to a solutions manual via the book's companion website"-- Provided by publisher.
Keywords: Reinforced concrete construction.; Buildings, Reinforced concrete.; elektronické knihy; electronic books